PENGARUH WORLDWIDE GOVERNANCE INDICATORS DAN MACROECONOMIC TERHADAP IHSG (Studi pada Negara Indonesia, Malaysia, Filipina, Singapura, dan Thailand Tahun 2004-2016) - Anisa Mutiah Razak; Suhadak Suhadak (Fakultas Ilmu Administrasi Universitas Brawijaya, 2019)
The purpose of this study was to know the influence of worldwide governance indicators and macroeconomic on the Jakarta Composite Index (JSI). The results of this study will illustrate whether Indonesia's IHSG performance can be influenced by worldwide governance indicators and macroeconomic of the countries of Indonesi, Malaysia, the Philippines, Singapore and Thailand. The type of research used is explanatory research. The location of the study was carried out in five sample countries that were selected according to purposive sampling criteria, namely five countries with the highest Gross Domestic Product (GDP) in Southeast Asia. The five countries are Indonesia, Malaysia, Philippines, Singapore and Thailand. The data used are secondary data on Voice and Accountability, Political Stability and Absence of Violence, Government Effectiveness, Regulatory Quality, Rule of Law, Control of Corruption, GDP, Inflation, Interest Rate, Exchange Rate, and IHSG.The data analysis technique used in this study is Partial Least Square (SmartPLS 3). The results of this study indicate that worldwide governance indicators affect macroeconomic conditions in Indonesia, Philippines, Singapore and Thailand. Worldwide governance indicators have no effect on the IHSG in Indonesia, Malaysia, Philippines and Thailand. Macroeconomic influences IHSG in Malaysia, Philippines and Thailand. Keywords: Worldwide Governance Indicators, Macroeconomic, JSI, Asia Tenggara. АBSTRАK Tujuan penelitian ini adalah untuk mengetahui pengaruh worldwide governance indicators dan macroeconomic terhadap IHSG. Hasil penelitian tersebut akan memberikan gambaran apakah kinerja IHSG Indonesia dapat dipengaruhi oleh worldwide governance indicators dan macroeconomic negara Indonesia, Malaysia, Filipina, Singapura, dan Thailand. Jenis penelitian yang digunakan adalah explanatory research. Lokasi penelitian dilakukan di lima negara sampel yang telah dipilih sesuai kriteria pengambilan sampel (purposive sampling), yaitu lima negara dengan Gross Domestic Product (GDP) tertinggi di Asia Tenggara. Kelima negara tersebut adalah Indonesia, Malaysia, Filipina, Singapura, dan Thailand. Data yang digunakan adalah data sekunder mengenai Voice and Accountability, Political Stability and Absence of Violence, Government Effectiveness, Regulatory Quality, Rule of Law, Control of Corruption, GDP, Inflation, Interest Rate, Exchange Rate, dan IHSG. Teknik analisis data yang digunakan pada penelitian ini adalah Partial Least Square (SmartPLS 3). Hasil penelitian ini menunjukkan bahwa worldwide governance indicators berpengaruh terhadap macroeconomic pada negara Indonesia, Filipina, Singapura dan Thailand. Worldwide governance indicators tidak berpengaruh terhadap IHSG pada negara Indonesia, Malaysia, Filipina, dan Thailand. Macroeconomic berpengaruh terhadap IHSG pada negara Malaysia, Filipina, dan Thailand. Kata kunci: Worldwide Governance Indicators, Macroeconomic, IHSG, Asia Tenggara, Indonesia.